Embryological Basis and Genetic Considerations of Right Lumbar Undescended Caecum with Paracaecal Appendix and Aberrant Vascular Supply - Verma, Anand; Patnaik, Madhumita; Ravi, Praveen Kumar; Biswas, Sayan; Gaikwad, Manisha R.; Manokaran, Aarthi (Acta medica Lituanica, 2026)
The caecum normally descends to the right iliac fossa during embryogenesis. Disruptions in midgut development may result in its atypical positioning. In a male cadaver, the small, conical caecum and paracaecal appendix were in the right lumbar region. The ileocaecal orifice was on the anterior caecal wall, and the appendicular orifice opened on the medial caecal wall inferior to it. The ascending colon was short and the hepatic flexure was inferior to hepatic quadrate lobe. The right colic artery was absent. The ascending branch of ileocolic artery supplied the caecum, and appendix. The disposition of the rest of the intestinal tract and peritoneum were observed, and measurements taken. Midgut development involves multiple regulatory genes, signalling pathways, transcription factors and mesenchyme-endoderm cross-talk. Mutations in several candidate genes were identified as contributing to midgut malrotation. Awareness of such rare anatomical variation is essential to avoid misdiagnosis of atypical appendicitis or intestinal obstruction.